PREVALENCIA DE LA HABRONEMOSIS GÁSTRICA EN CABALLOS PERUANOS DE PASO, ZONA SUR DE LIMA - Sánchez-Silva M., Silvana (2003)
The objective of the present study was to determine the prevalence of gastric habronemiasis on the Peruvian Paso Horse population reared in the southern part of Lima. Fecal samples were collected from 264 equines of different age, sex and location and were processed by the Xenodiagnosis technique. Forty five equines were positive to habronemiasis, which means a prevalence of 17.1 ± 2.0% (C.I. 95%). There was a significant relationship between the presence of Habronema muscae with sex and place of origin of the animals (p<0.05), but not with the age of the animal (p>0.05).